A Borel linear subspace of R^ω that cannot be covered by countably many closed Haar-meager sets - Banakh, Taras; Jabłońska, Eliza (Topological Methods in Nonlinear Analysis, 2024)
We prove that the countable product of lines contains a Haar-null Haar-meager Borel linear subspace L that cannot be covered by countably many closed Haar-meager sets. This example is applied to studying the interplay between various classes of ``large’’ sets and Kuczma-Ger classes in the topological vector spaces R^n for nω.